Hydrogel scaffolds in bone regeneration: Their promising roles in angiogenesis - Liu, Jun; Yang, Lili; Liu, Kexin; Gao, Feng (Frontiers in Pharmacology, 2023)
Bone tissue engineering (BTE) has become a hopeful potential treatment strategy for large bone defects, including bone tumors, trauma, and extensive fractures, where the self-healing property of bone can not repair the defect. BTE is composed of three main elements: progenitor/stem cells, scaffold, and growth factors/biochemical cues. Among the various biomaterial scaffolds, hydrogels are broadly used in BTE owing to their biocompatibility, controllable mechanical characteristics, osteoconductive, and osteoinductive properties. During BTE, angiogenesis plays a central role in the failure or success of bone reconstruction via discarding wastes and providing oxygen, minerals, nutrients, and growth factors to the injured microenvironment. This review presents an overview of BTE and its requirements, hydrogel structure and characterization, the applications of hydrogels in bone regeneration, and the promising roles of hydrogels in bone angiogenesis during BTE.